Solvent‐Driven Supramolecular Wrapping of Self‐Assembled Structures. (21st January 2021) - Moreno‐Alcántar, Guillermo; Aliprandi, Alessandro; Rouquette, Remi; Pesce, Luca; Wurst, Klaus; Perego, Claudio; Brüggeller, Peter; Pavan, Giovanni M.; De Cola, Luisa
Abstract: Self‐assembly relies on the ability of smaller and discrete entities to spontaneously arrange into more organized systems by means of the structure‐encoded information. Herein, we show that the design of the media can play a role even more important than the chemical design. The media not only determines the self‐assembly pathway at a single‐component level, but in a very narrow solvent composition, a supramolecular homo‐aggregate can be non‐covalently wrapped by a second component that possesses a different crystal lattice. Such a process has been followed in real time by confocal microscopy thanks to the different emission colors of the aggregates formed by two isolated Pt II complexes. This coating is reversible and controlled by the media composition. Single‐crystal X‐ray diffraction and molecular simulations based on coarse‐grained (CG) models allowed the understanding of the properties displayed by the different aggregates. Such findings could result in a new method to construct hierarchical supramolecular structures. Abstract : Taking advantage of the useful emitting features of two platinum complexes, we show how the media regulates the assembly pathways from self‐sorting to an unprecedented reversible, dynamic molecular wrapping of a complex on another other assembled structure.